Relação do indicador da situação financeira do modelo Fleuriet e o valor das empresas não financeiras de capital aberto da BM&FBOVESPA (2010-2013) - Vendramel Junior, Osmar (2014)
The theory of Dynamic Model, introduced in the decade of 70, through the reclassification of balance sheets in operating cycle, permanent and treasury accounts evaluates and classifies, quickly and simplified, the finance situation of the companies in six possible types: I - Excellent; II - Solid; III - Unsatisfactory; IV - High Risk; V Too Bad; and VI Very Bad. The present study search if exists the relationship between the rating calculated according to Fleuriet model with the value market of the not financial public traded Brazilian companies, during 2010 to 2013, using the multiple regression method. For that, It was defined the market value of the company such as dependent variable and the classification of Fleuriet Model as independent variable. The study used two samples, the first one with all public companies, total of 305, and the second with the 53 companies of the IBOVESPA index in dec.31.2013. The main result was that the market value was related with the financial rate situation calculated through the Dynamic Model and this relationship is negative. The worse is the financial classification ratio, the lowest is the value market of the company. The main limitation of the study was the lack of previous Fleuriet model studies using the multiple regression analysis and for future studies would be interesting to extend the sample used, including closed capital firms and increasing the years analyzed